Association of Plaque Inflammation With Stroke Recurrence in Patients With Unproven Benefit From Carotid Revascularization. (12th July 2022) - Camps-Renom, Pol; McCabe, John; Martí-Fàbregas, Joan; Giannotti, Nicola; Fernández-León, Alejandro; McNulty, Jonathan P.; Baron, Jean-Claude; Barry, Mary; Coutts, Shelagh B.; Cronin, Simon; Delgado-Mederos, Raquel; Dolan, Eamon; et al.
Abstract : Background and Objectives: In pooled analyses of endarterectomy trials for symptomatic carotid stenosis, several subgroups experienced no net benefit from revascularization. The validated symptomatic carotid atheroma inflammation lumen-stenosis (SCAIL) score includes stenosis severity and inflammation measured by PET and improves the identification of patients with recurrent stroke compared with lumen-stenosis alone. We investigated whether the SCAIL score improves the identification of recurrent stroke in subgroups with uncertain benefit from revascularization in endarterectomy trials. Methods: We did an individual-participant data pooled analysis of 3 prospective cohort studies (Dublin Carotid Atherosclerosis Study [DUCASS], 2008–2011; Biomarkers and Imaging of Vulnerable Atherosclerosis in Symptomatic Carotid Artery Disease [BIOVASC], 2014–2018; Barcelona Plaque Study, 2015–2018). Eligible patients had a recent nonsevere (modified Rankin Scale score ≤3) anterior circulation ischemic stroke/TIA and ipsilateral mild carotid stenosis (<50%); ipsilateral moderate carotid stenosis (50%–69%) plus at least 1 of female sex, age <65 years, diabetes mellitus, TIA, or delay >14 days to revascularization; or monocular loss of vision. Patients underwent coregistered carotid 18 F-fluorodeoxyglucosePET/CT angiography (≤7 days from inclusion). The primary outcome was 90-day ipsilateral ischemic stroke. Multivariable Cox regression modeling was performed. Results: We included 135 patients. All patients started optimal modern-era medical treatment at admission, and 62 (45.9%) underwent carotid revascularization (36 within the first 14 days and 26 beyond). At 90 days, 18 (13.3%) patients had experienced at least 1 stroke recurrence. The risk of recurrence increased progressively according to the SCAIL score (0.0% in patients scoring 0–1, 15.1% scoring 2–3, and 26.7% scoring 4–5; p = 0.04). The adjusted (age, smoking, hypertension, diabetes, carotid revascularization, antiplatelets and statins) hazard ratio for ipsilateral recurrent stroke per 1-point SCAIL increase was 2.16 (95% CI 1.32–3.53; p = 0.002). A score ≥2 had a sensitivity of 100% for recurrence. Discussion: The SCAIL score improved the identification of early recurrent stroke in subgroups who did not experience benefit in endarterectomy trials. Randomized trials are needed to test whether a combined stenosis-inflammation strategy will improve selection for carotid revascularization when benefit is currently uncertain. Classification of Evidence: This study provides Class II evidence that, in patients with recent anterior circulation ischemic stroke who do not benefit from carotid revascularization, the SCAIL score accurately distinguishes those at risk for recurrent ipsilateral ischemic stroke.